Mapping the RP10 locus for autosomal dominant retinitis pigmentosa on 7q: refined genetic positioning and localization within a well-defined YAC contig. - McGuire, R E; Jordan, S A; Braden, V V; Bouffard, G G; Humphries, P; Green, E D; Daiger, S P

(untitled) (Genome Research, 1996)
Retinitis pigmentosa is a genetically heterogeneous disease that has autosomal dominant, autosomal recessive and X-linked forms. Autosomal dominant retinitis pigmentosa (adRP) has thus far been associated with eight distinct loci, including the rhodopsin and peripherin/RDS genes as well as unidentified genes on chromosomes 7p, 7q, 8q, 17p, 17q, and 19q. The RP10 locus for adRP on chromosome 7q was first mapped in a Spanish family; later, an unrelated American family was identified that also showed linkage to 7q. By combining the linkage results from both families, we are able to assign the disease gene to a 5-cM interval on 7q. Based on extensive physical mapping of this region, the genetic interval is now fully contained within a approximately 5-Mb segment on a well-defined YAC contig. These studies significantly reduce the size of the RP10 critical region, exclude a number of possible candidate genes, and provide the necessary cloned DNA for the positional cloning of the RP10 gene.